APLIKASI TEKNOLOGI PENGINDERAAN JAUH UNTUK PEMANTAUAN REVEGETASI LAHAN REKLAMASI TAMBANG - Mulkal; Alisastromijoyo; Nurul Aflah (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2022)
Following the regulation of the Indonesian Government, every Mining company has an obligation to do reclamation for mining areas that had been exploited. One of the reclamation stages is re-vegetation to plant the exploited mine area with cover crops. Cover crop monitoring commonly is taken by direct assessment of plants growth. However, this approach is ineffective and also expensive which is proportional to the large reclamation area. The objective of this research is to apply remote sensing methods to monitor cover crop growth at Siltstone Quarry of PT Aroma Cipta Anugrahtama, in Lhoknga subdistrict, Aceh Besar. The monitoring was conducted using Sentinel-2 satellite imagery data by computing the Normalized Difference Vegetation Index (NDVI). The analysis was done in a time series from the year 2019 to 2022 using the Google Earth Engine (GEE) cloud platform. The result shows that the NDVI value is varied from 0 to 0,8 which is classified into no vegetation to high vegetation area. Based on spatial distribution of NDVI values, can be observed that the northern area has higher uniform NDVI value compared to the southern area which is more mixed. This indicates the southern part has been exploited earlier. Overall the re-vegetation successful rate for reclamation zone before 2019, 2019, 2020, 2021 and 2022 are 96%, 99,5%, 70,6%, 36,6% and 6,2%.